Análise de agrotóxicos e Acibenzolar-S-Metílico (ASM) em Apis mellifera L. (Hymenoptera: Apidae) e a ação de ASM na indução de resistência em soja - Sampaio, Amanda Roberta (2020)
Bees are the most important pollinators, especially Apis mellifera L. (Hymenoptera: Apidae), however, the excessive use of pesticides has been an adversity to these organisms. For this reason, soybean cultivation is one of the threats to this species. Resistance induction seeks to reduce the use of pesticides, in this crop and others, by activating the defense of the plant. Acibenzolar-S-methyl (ASM) is a resistance inducer with no recommendation for soybeans and unknown as to its toxicity to bees. Thus, this study aimed to evaluate the relationship between the use of pesticides and the mortality of A. mellifera using a meta-analytical review, to evaluate the effects of acibenzolar-S-methyl on the survival and flight of Africanized A. mellifera forages and for the expression of the β-1,3-glucanase gene in soybeans. By a meta-analysis with 154 data sets from 1951 to 2019 it was possible to confirm the relationship between A. mellifera mortality and the use of pesticides. The method of application and the class of insecticides with the greatest impact on the survival of these insects, respectively, is direct spraying, and insecticides. ASM was tested for selectivity to A. mellifera forage bees (feeding, spraying and contact), in five concentration (20, 40, 60, 80 and 100% of the field dose), in addition to the control (autoclaved distilled water). In addition, 30 bees that remained in contact with the field dose for two hours were evaluated for flight capacity after 48 hours. Honeybees fed and which came into contact with field doses of ASM did not have their survival reduced when compared to the control. Honeybee survival was significantly reduced from the lowest dose (20%) when ASM was sprayed on the honeybees. Flight capacity has not been changed. ASM has also been tested as a soy resistance inducer, for the expression of the soybean SGlu5 gene, responsible for β-1,3-glucanase production. For this, an experiment was carried out in a greenhouse, eight pots with autoclaved soil received 60 soybean seeds each. Only the most vigorous plants were maintained and, when the crop cycle reached V2-V3, ASM (considered zero time) was applied in half of plants/ pots. After 24 hours, the fungus Phakopsora pachyrhizi was inoculated and, for nine days, collections of plant material were performed. This material was taken to the laboratory, extracted RNA, transformed into cDNA and later, evaluated for gene expression by RT-qPCR. It was found that ASM is not efficient for the expression of the SGlu5 gene, but P. pachyrhizi activated and increased the expression of this gene. Pesticides have negative effects on A. mellifera, relatade to this insect mortality. The use of ASM in a field dose reduces the survival of A. mellifera when direct spray, however, when the Africanized honeybees come into contact or feeding diet with ASM, there are no negative effects, neither in of these insects. Moreover, ASM doesn’t have effect on the expression of the SGlu5 gene in soybean.